PENCAK SILAT SEBAGAI MEDIA DAKWAH - Bambang Iswahyudi (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
Pencak Silat Pagar Nusa has twelve movements in the opening greeting which have their own meaning and purpose in each movement. The whole movement is aimed at conveying the message of da'wah to every Pagar Nusa santri so that it can be practiced so that it can be useful for the society an to each other. This study uses the semiotic theory of Ferdinand De Saussure which explains that a sign is something in a physical form that can be seen and heard which usually refers to an object or aspect of reality to be communicated. Saussure also revealed that the signifier and the signified are a unity that are interrelated and cannot be separated. The results of this study indicate that the opening greeting movement from Pagar Nusa is a da'wah that is implied in every movement that contains the practice of Ahlussunah wal jama'ah from Nahdlatul Ulama'. Thus this study can be used as a reference to indentified a da’wah on other pencak silat movement